2019
DOI: 10.1002/pmic.201800368
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of a Monocot Acyl‐CoA‐Binding Protein Confers Broad‐Spectrum Pathogen Protection in a Dicot

Abstract: Plants are continuously infected by various pathogens throughout their lifecycle. Previous studies have reported that the expression of Class III acyl-CoA-binding proteins (ACBPs) such as the Arabidopsis ACBP3 and rice ACBP5 were induced by pathogen infection. Transgenic Arabidopsis AtACBP3-overexpressors (AtACBP3-OEs) displayed enhanced protection against the bacterial biotroph, Pseudomonas syringae, although they became susceptible to the fungal necrotroph Botrytis cinerea. A Class III ACBP from a monocot, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 86 publications
(104 reference statements)
4
25
0
Order By: Relevance
“…In contrast, during the setup of an arbuscular mycorrhizal symbiosis between Medicago truncatula and Glomus versiforme , the induction of an XTH gene was observed [ 124 ]. XTH genes are involved in plant defense responses to inoculation by pathogenic fungi, as evidenced by interactions between Arabidopsis and the necrotrophic Rhizoctonia solani (the causal agent of root rot disease), between wild jute species and the hemibiotrophic Macrophomina phaseolina (causing stem rot disease), and between sugarcane and a biotrophic Sporisorium scitamineum (responsible for culmicolous disease) [ 125 , 126 , 127 ]. XTH genes were also revealed to be involved in the phloem response to aphid infestation of celery ( Apium graveolens ) and Arabidopsis [ 128 , 129 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, during the setup of an arbuscular mycorrhizal symbiosis between Medicago truncatula and Glomus versiforme , the induction of an XTH gene was observed [ 124 ]. XTH genes are involved in plant defense responses to inoculation by pathogenic fungi, as evidenced by interactions between Arabidopsis and the necrotrophic Rhizoctonia solani (the causal agent of root rot disease), between wild jute species and the hemibiotrophic Macrophomina phaseolina (causing stem rot disease), and between sugarcane and a biotrophic Sporisorium scitamineum (responsible for culmicolous disease) [ 125 , 126 , 127 ]. XTH genes were also revealed to be involved in the phloem response to aphid infestation of celery ( Apium graveolens ) and Arabidopsis [ 128 , 129 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has shown that transgenic Arabidopsis overexpressing OsACBP5 were conferred resistance to necrotrophic ( R. solani, B. cinerea, A. brassicicola ), hemibiotrophic ( C. siamense ) and biotrophic ( P. syringae ) phytopathogens 59 , 60 . Proteomic analysis on the R. solani- infected transgenic Arabidopsis OsACBP-OEs showed upregulation of biotic stress-related proteins including cell wall-related proteins such as FASCILIN-LIKE ARABINOGALACTAN-PROTEIN10, LEUCINE-RICH REPEAT EXTENSIN-LIKE PROTEINS, XYLOGLUCAN ENDOTRANSGLUCOSYLASE/HYDROLASE PROTEIN4 and PECTINESTERASE INHIBITOR18; proteins associated with glucosinolate degradation including GDSL-LIKE LIPASE23, EPITHIOSPECIFIER MODIFIER1, MYROSINASE1, MYROSINASE2 and NITRILASE1; as well as a protein involved in jasmonate biosynthesis, ALLENE OXIDE CYCLASE2 59 , 60 . These results from proteomic analysis indicated that the defence responses arising from OsACBP5 overexpression in transgenic Arabidopsis involved cell wall-mediated defence as well as salicylic acid (SA)- and jasmonic acid (JA)-mediated defence pathways 59 , 60 .…”
Section: Discussionmentioning
confidence: 99%
“…Rice blast is a destructive fungal disease causing a 30% decline in rice production globally 58 . Our recent study demonstrated that overexpression of OsACBP5 in transgenic Arabidopsis conferred resistance to representative necrotrophic ( R. solani, B. cinerea, Alternaria brassicicola ), hemibiotrophic ( Colletotrichum siamense ) and biotrophic ( P. syringae ) phytopathogens through cell wall-mediated defence as well as SA- and JA-mediated defence pathways 59 , 60 . Given the need for crops to be protected against necrotrophic fungal pathogens, the present study follows up on our initial investigations on OsACBP5 31 .…”
Section: Introductionmentioning
confidence: 99%
“…Preparation of protein extracts from Arabidopsis roots and mass spectrometry analysis of peptides were performed as previously described (Zhu et al , 2016; Panthapulakkal Narayanan et al , 2019). A global false discovery rate (FDR) (<1%) was used as the criterion to accept peptide assignments and protein identifications (Zhu et al , 2016; Panthapulakkal Narayanan et al , 2019). Four biological repeats of 7-day-old Arabidopsis roots treated with F-244 (2 µM) or DMSO (control) for 4 d were used.…”
Section: Methodsmentioning
confidence: 99%